Faktor Penyebab dan Mekanisme Penyelesaian Sengketa Tanah Warisan: (Studi Kasus: Kampung Ulayat Mbehal Menjerite, Kecamatan Boleng, Kabupaten Manggarai Barat) - Dionisius Hadimarino Ramli; Orpa J. Nobatonis; Helsina Fransiska Pello (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this research is to analyze the causal factors and mechanisms for resolving inherited land disputes. The type of research in this study is empirical legal research with data collection through observation, interviews. The results of this research are the factors causing inheritance land disputes in Kampung Ulayat, Mbehal Menjerite, Boleng District, West Manggarai Regency are the Uncertainty of Land Certification Uncertainty regarding land ownership in this area is caused by the lack of legal land registration at the National Land Agency (BPN). This is contrary to the provisions in the Basic Agrarian Law (UUPA) Without a valid certificate, ownership rights become weak and vulnerable to disputes and also the unilateral sale of land without the consent of all heirs potentially violates their rights. The mechanism for resolving inherited land disputes in the indigenous community of Kampung Ulayat, Mbehal Menjerite, Boleng District, West Manggarai Regency is mediation, which is an important first step in resolving land disputes. Indonesian civil law encourages dispute resolution through mediation to avoid prolonged conflict. However, the results of mediation sometimes do not satisfy all parties and in court heirs who feel aggrieved can file a lawsuit to claim their rights.